Profesonalisme Guru Dalam Membentuk Karakter Religius Siswa Di Mi Izzul Islam Krejengan Probolinggo - Tutik Hidayati; Endah Tri wisudaningsih Endah Tri Wisudaningsih; Nani Zahrotul Mufidah (eL Bidayah: Journal of Islamic Elementary Education, 2023)
The aim of the research is to describe the professional competence of teachers in shaping the religious character of students at MI Izzul Islam Krejengan Probolinggo and how the religious character of students is at MI Izzul Islam. The method used by researchers uses a qualitative approach. While the type of research is a case study. The data obtained by researchers came from teachers at Mi Izul Islam and Mi Izzul Islam students. In collecting data, researchers used observation techniques, interviews, and documentation. In compiling and analyzing the data obtained from data collection techniques, researchers use observation, data reduction, and conclusions. Based on the results of the research the researchers described, it can be concluded that teacher professionalism in shaping the religious character of students at MI Izzul Islam is included in the good category, teachers are able to apply four indicators of teacher professional competence, namely pedagogic competence, personality competence, social competence, and professional competence in the process of implementing learning in the school environment, class, and community. The pedagogic competence of teachers at MI Izzul Islam can form the character of jihad in students such as enthusiasm, discipline, and being active in learning, the personality competencies of teachers at MI Izzul Islam can form religious characters in students such as sincerity, istiqomah, and tawadhu', the social competence of teachers in MI Izzul Islam can shape the tolerance character of students, and in the professional competence of teachers at MI Izzul Islam are able to master the material in depth according to the standard content of the education unit program, subjects and subject groups, master strategies and learning methods. The character of students at mi izul Islam is having a sincere attitude, istiqamah, jihad, intention because of Allah, tawadhu', and tolerant [ Penelitian bertujuan untuk mendeskripsikan kompetensi profesionalisme guru dalam membentuk karakter religius siswa di MI Izzul Islam Krejengan Probolinggo dan bagaimana karakter religius siswa di mi izzul islam. Metode yang di gunakan peneliti menggunakan pendekatan kualitatif. Sedangkan jenis penelitiannya yaitu study kasus. Data yang di peroleh peneliti bersumber dari guru di Mi Izul Islam dan siswa Mi Izzul Islam. Dalam mengumpulkan data, peneliti menggunakan teknik observasi, wawancara, dan dokumentasi. Dalam menyusun dan menganalisis data yang di peroleh dari teknik pengumpulan data, peneliti menggunakan pengamatan, reduksi data, dan kesimpulan. Berdasarkan hasil penelitian peneliti paparkan maka dapat diambil kesimpulan bahwa profesionalisme guru dalam membentuk karakter religius siswa di MI Izzul Islam sudah termasuk kategori baik, guru sudah dapat mengaplikasikan empat indikator kompetensi professional guru yaitu kompetensi pedagogik, kompetensi kepribadian, kompetensi social, dan kompetensi professional di dalam proses pelaksanaan pembelajaran di lingkungan sekolah, kelas, dan masyarakat. Kompetensi pedagogik guru di MI Izzul Islam dapat membentuk karakter jihad pada siswa seperti semangat, disiplin, dan giat dalam belajar, kompetensi kepribadian guru di MI Izzul Islam dapat membentuk karakter religius pada siswa seperti ikhlas, istiqomah, dan tawadhu’, kompetensi sosial guru di MI Izzul Islam dapat membentuk karakter toleransi siswa, dan dalam kompetensi profesional guru di MI Izzul Islam mampu menguasai materi secara mendalam sesuai standar isi program satuan pendidikan, mata pelajaran, dan kelompok mata pelajaran, menguasai strategi, dan metode pembelajaran. Adapun karakter siswa di mi izul islam yaitu memiliki sikap ikhlas, istiqamah, jihad, niat karna allah, tawadhu’, dan toleran]